Intensifikasi Budidaya Perikanan (Osphronemus Gouramy) Mandiri Berbasis Sumberdaya Lokal sebagai Upaya Peningkatan Produktivitas POKDAKAN Mina Sida Karya - Bimantara, Arif; Zuhdi, M. Nurdin; Tunggali, Ade Putranto Prasetyo Wijiharto; Manasikana, Rinta Arina (Universitas Muhammadiyah Surakarta, 2024)
Mina Sida Karya Fish Cultivation Group (POKDAKAN) operates in Sidamulih Village, Rawalo District, Banyumas Regency, Central Java, employing an extensive, traditional fish farming system that yields low productivity. This group faces four significant challenges that necessitate attention: (1) Insufficient knowledge and skills among partners in intensive gourami fish farming management to enhance POKDAKAN Mina Sida Karya's productivity; (2) Lack of a consistent water supply for cultivation throughout the year; (3) Limited knowledge in producing cost-effective natural and artificial feed; (4) Inadequate expertise in marketing partner products, resulting in a restricted market reach. Addressing these challenges, service activities have been implemented using Participatory Learning and Action (PLA). These include (1) providing assistance and training in intensive gourami fish farming management to boost cultivation productivity; (2) drilling boreholes up to 75 meters deep to secure a year-round water source; (3) conducting training sessions on independent feed production, both artificial and natural Daphnia sp., enabling partners to generate their own feed; (4) establishing digital branding systems through social media platforms to expand market presence. This aims to increase the productivity of the Mina Sida Karya Fish Farming Group. The activities that have been carried out have significantly impacted the Mina Sida Karya POKDAKAN with a percentage of 57.14% of participants stating that they have sufficient knowledge about intensive osphronemus gouramy fish farming, 61.90% stating that they have no difficulty in obtaining water supply, 52.38% stating that they know how to produce efficient and cost-effective natural feed, and 66.67% stating that they are satisfied with the market reach of fish products.